Food Safety and Health from the Perspective of Islam - Hamed Biglari; Abdollah Dargahi; Yaser Vaziri; Reyhaneh Ivanbagha; Mahsa Hami; Mohsaen Poursadeqiyan (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: The relationship between food and the health of the soul and body is one of the issues mentioned in a monotheistic worldview including Islam. The verse "And We send down of the Qur'an that which is healing and mercy for the believers" confirms the influence of religious teachings in this respect. This study examines the Qur'anic guidelines on food safety and hygiene. Methods: This review study investigates into the health system through library reviews of authentic sources, religious teachings, Quranic verses, authentic statements from the infallibles (Imams and the prophet), important Qur'anic commentaries, statements and books on nutrition on national and international databases. After categorization, the results were analyzed and integrated. The authors declared no conflict of interest. Results: About 250 Qur'anic verses and dozens of statements from the infallibles point to the importance of food and nutrition. The Holy Qur'an mentions the word "food" 48 times, the word "eating" 107 times, and the word "drink" 39 times. In the verses related to food, it has been mentioned six times that food should be Halal, and in various interpretations, the importance of nourishing the body is emphasized. Attitude to food as a sign in knowing God, believing in divine generosity, enjoying divine intent, asserting the rights of those in need, clean eating, having a balanced diet, adhering to halal food, and avoiding forbidden foods are the most important attitudinal and habitual strategies related to food safety. In addition, human dignity is one of the most important outcomes of adhering to Islamic food safety strategies. Conclusion: Since in revelatory doctrines, a healthy diet involves physical, mental, spiritual and social aspects of human life, it is essential that health policy makers consider the Islamic nutritional approach to achieve a true universal health. For downloading the full-text of this article please click here. Please cite this article as: Biglari H, Dargahi A, Vaziri Y, Ivanbagh R, Hami M, Poursadeqiyan M. Food Safety and Health from the Perspective of Islam. Journal of Pizhūhish dar dīn va salāmat. 2020;6(1):131-143.https://doi.org/10.22037/jrrh.v6i1.19142